The Politics of Eroticism: Political Writing and Arundhati Roy's The God of Small Things - Thapa, Dharma (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
This article analyses the erotic relationships between sexes depicted in Arundhati Roy’s novel The God of Small things in the binary opposition: those based on bourgeois patriarchal dominance and that based on equality and mutual respect. It focuses on the relationship between Ammu and Velutha as love, in diametrical contrast with the former pattern, based on independent choices and guided and inspired by radical politics. DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10468 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013; 51-58